1999
DOI: 10.1080/j.1600-0412.1999.780910.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of labor with mifepristone, - A randomized, double-blind study versus placebo

Abstract: The results of the present study show that mifepristone is a simple and effective treatment for inducing labor in post-term women with an unripe cervix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 0 publications
3
20
0
2
Order By: Relevance
“…In our study, we observed that mifepristone is associated with favorable outcome in 89 % of women (labor onset in 56 % and cervical ripening 33 %) within 48 h of administration of oral mifepristone. These observations are in accordance with the existing literature where a variable success rate of labor onset at 66-93 % has been observed in pregnant women [8][9][10][11][12][13][14][15]. Also, the effect of cervical ripening after use of mifepristone has been variable ranging from no statistically difference to statistically significant improvement (60-80 % of all cases) [16][17][18][19][20].…”
Section: Discussionsupporting
confidence: 80%
“…In our study, we observed that mifepristone is associated with favorable outcome in 89 % of women (labor onset in 56 % and cervical ripening 33 %) within 48 h of administration of oral mifepristone. These observations are in accordance with the existing literature where a variable success rate of labor onset at 66-93 % has been observed in pregnant women [8][9][10][11][12][13][14][15]. Also, the effect of cervical ripening after use of mifepristone has been variable ranging from no statistically difference to statistically significant improvement (60-80 % of all cases) [16][17][18][19][20].…”
Section: Discussionsupporting
confidence: 80%
“…According to various existing literature, the labor onset and cervical ripening observed. [8][9][10][11][12] There is need of oxytocin requirement for augmentation of labour is very minimum so there is very less chances of scar dehiscence and rupture uterus. Mifepristone initiate the labour as naturally, causes cervical ripening (by releasing NO),promote uterine contractions by forming gap junctions and increasing influx of calcium it also increases the prostaglandins release without acting as a direct uterotonic.…”
Section: Discussionmentioning
confidence: 99%
“…In six trials women in the two arms of the studies were given different interventions and therefore blinding was not feasible, or not attempted (Gittens 1996;Harper 2006;Meyer 2005;Newman 1997;Stenlund 1999). The lack of blinding in these studies may have affected some of the outcomes examined in the review.…”
Section: Risk Of Bias In Included Studiesmentioning
confidence: 99%
“…We included five studies in this comparison (Elliott 1998;Giacalone 1998;Lelaidier 1994;Stenlund 1999). Women in the mifepristone group were less likely to require further medication to induce labour compared with controls ((random-effects) RR 0.59, 95% CI 0.37 to 0.95).…”
Section: Primary Outcomesmentioning
confidence: 99%
See 1 more Smart Citation